Pengaruh Motivasi dan Media Pembelajaran Terhadap Hasil Belajar Siswa SMA Kelas XI pada Materi Kesetimbangan Kimia - Eli Ester Pangaribuan; Iis Siti Jahro (Jurnal Pendidikan Kimia FKIP Universitas Halu Oleo, 2024)
This research aims to describe the influence of motivation and learning media on the learning outcomes of class XI high school students on chemical equilibrium material. The population in this study were all students in class XI MIPA at SMA Negeri 2 Medan. The method in this research is a quasi-experiment with Pretest Posttest Control Group Design, class samples were selected using random sampling techniques and student samples were selected using purposive sampling, obtained class XI MIPA 1 as experimental class 1 and XI MIPA 8 as experimental class 2. Influence of motivation and learning media were analyzed using normality, homogeneity and hypothesis tests. The research results show that there is an interaction between motivation and learning media and there is an influence of motivation and learning media on high school students' learning outcomes.